1995
DOI: 10.1038/nsb0695-466
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray structure of an anti-tumour antibody in complex with antigen

Abstract: The crystal structures of the murine BR96 Fab and its human chimera have been determined in complex with the nonoate methyl ester derivative of Lewis Y (nLey) at 2.8 A and 2.5 A resolution, respectively. BR96 binds the carbohydrate in a large pocket which is formed by residues of all CDR loops except L2. The binding of the carbohydrate is mediated predominantly by aromatic residues in BR96. Analysis of the structure suggests that BR96 is capable of recognizing a structure larger than the Le(y) tetrasaccharide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
60
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 32 publications
3
60
0
1
Order By: Relevance
“…This hypothesis was later confirmed by solution measurements of the binding of anti-1,6-dextran Igs (30 -32). Although sharing some of these features, the only two other anti-carbohydrate Abs for which the structure has been determined in complex with Ag, Se155 (14) and BR96 (16), are both specific for a determinant consisting of multiple saccharides of nonlinear polysaccharides, the Salmonella O-Ag and the Lewis Y Ag, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was later confirmed by solution measurements of the binding of anti-1,6-dextran Igs (30 -32). Although sharing some of these features, the only two other anti-carbohydrate Abs for which the structure has been determined in complex with Ag, Se155 (14) and BR96 (16), are both specific for a determinant consisting of multiple saccharides of nonlinear polysaccharides, the Salmonella O-Ag and the Lewis Y Ag, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, the extensive immunochemical data available on anti-carbohydrate Abs (10 -13) contrasts with the paucity of structural information on these types of systems, because to date only two carbohydrate-specific Abs have been studied in complex with ligands, namely the mAb Se155-4 specific for a Salmonella serotype-B O-Ag (14,15) and the antitumor Ab BR96 (16). To gain further insight into the structural basis of carbohydrate recognition and to understand V. cholerae serotype specificity, we have undertaken crystallographic studies of protective anti-cholera Abs in complex with synthetic analogs of the O-Ag.…”
mentioning
confidence: 99%
“…All three residues are engaged in only two direct and two watermediated hydrogen bonds with the Fab. The hydrogen bond and other contacts between His P6 side chain and Lys L50 NZ, the first residue of the short loop CDR L2, are unusual in that this loop makes no contact with the saccharide in this or other complexes of antibody with carbohydrates (23,24) or haptens (25,26). The Ala P7 methyl side chain lies close to, but not completely inside, a small hydrophobic cavity (Tyr L32 and His L27D) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One means of exploring this question is to attempt to generate mutant anti-carbohydrate antibodies with higher affinities, either by design of site-directed mutants or by randomizing selected codons in a phage library. However, the production of antibodies with improved affinities that maintain antigen specificity has proven challenging (1)(2)(3)(4). For example, in an exhaustive site-directed mutagenesis study of CDR 1 H3 of an anti-Salmonella Fab, Brummell et al (1) found that all of the 90 mutant Fabs produced showed similar or decreased binding affinity for the O-antigen.…”
mentioning
confidence: 99%
“…For example, in an exhaustive site-directed mutagenesis study of CDR 1 H3 of an anti-Salmonella Fab, Brummell et al (1) found that all of the 90 mutant Fabs produced showed similar or decreased binding affinity for the O-antigen. Mutants of the anti-Lewis Y antibody BR96 were obtained as phage-displayed scFv; although the mutant scFv binding affinity had increased by up to 6-fold versus the native antibody, its specificity was altered (2,3). More recently, higher affinity antibodies against levan, a model for the polysaccharide capsules of bacteria, were obtained by mutational analysis though their fine specificity varied from that of the parent antibody (5).…”
mentioning
confidence: 99%